English planning in crisis : 10 steps to a sustainable future - Ellis, Hugh; Henderson, Kate (Policy Press shorts. Policy & practice., 2016)
This book is a manifesto for a new planning system in England. Reflecting on controversial new Government reforms and deregulation, the authors draw on policy and practice examples from across the UK and internationally to challenge the current English system and ignite debate about its future.